Cellular and cytoskeletal heterogeneity along the rat ventral prostatic duct. - Rouleau, Michèle. (University of Ottawa (Canada), 1990)
In this study, the ductal heterogeneity in the rat ventral prostate was further investigated in terms of structural elements that make up the different cell types of the prostate as well as cell populations found along prostatic ducts. In addition, effects of androgens were analyzed in specific locations of the ductal-acinar network. The cytokeratin content of the prostate was characterized biochemically and by immunofluorescence and was used as a marker to monitor the behaviour of each cell type after androgen depletion. It was found that the cytokeratin content of basal and luminal epithelial cells are characteristic for each cell type and that these structural proteins constitute good markers for these cell types. Using antibodies specific for basal and luminal epithelial cells, the ratio basal to luminal epithelial cells was shown to vary along the prostatic duct as well as after castration, suggesting a preferential loss of luminal epithelial cells. Based on the observations of the cellular dynamics in the prostate of intact versus castrated rats, a model of regression is proposed. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.